Transidentalisme Seni dan Budaya: Kajian Apresiasi Kritis Estetika Islam - W. Waluyo (Jurnal Penelitian, 2018)
This article discusses about art from the point of view of Islamic spirituality. This is a study of the most important aspects of an art inspired by Islamic values, including literature, music, and other forms of art. Thus the deeper a person penetrates the meaning of Islamic art, the wider one understands of the relationship between art and Islamic spirituality. Arts are then refined by Islamic conception. Islam blesses every work of art that is in compliance with the Islamic teaching. The blessed works form a unique way of life that is in accordance with the norms of Islamic values. Acculturation of arts and local culture according to Islam is not value free, rather it is value bound.